2013
DOI: 10.1016/j.taap.2013.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary instillation of low doses of titanium dioxide nanoparticles in mice leads to particle retention and gene expression changes in the absence of inflammation

Abstract: We investigated gene expression, protein synthesis, and particle retention in mouse lungs following intratracheal instillation of varying doses of nano-sized titanium dioxide (nano-TiO2). Female C57BL/6 mice were exposed to rutile nano-TiO2 via single intratracheal instillations of 18, 54, and 162μg/mouse. Mice were sampled 1, 3, and 28days post-exposure. The deposition of nano-TiO2 in the lungs was assessed using nanoscale hyperspectral microscopy. Biological responses in the pulmonary system were analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
118
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(130 citation statements)
references
References 37 publications
12
118
0
Order By: Relevance
“…The strong inflammatory and acute phase responses are not unique to MWCNT exposure. Similar responses have been observed following exposure to nano-titanium dioxide particles (nano-TiO 2 ) and nano-carbon black (nano-CB) particles via instillation or inhalation using experimental designs similar to that used in the present study (Bourdon et al, 2012a;Halappanavar et al, 2011;Husain et al, 2013;Jackson et al, 2011b). However, the number of differentially expressed genes was an order of magnitude greater following exposure to the two MWCNTs than following exposure to nano-TiO 2 and nano-CB, indicating stronger potency of MWCNT.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The strong inflammatory and acute phase responses are not unique to MWCNT exposure. Similar responses have been observed following exposure to nano-titanium dioxide particles (nano-TiO 2 ) and nano-carbon black (nano-CB) particles via instillation or inhalation using experimental designs similar to that used in the present study (Bourdon et al, 2012a;Halappanavar et al, 2011;Husain et al, 2013;Jackson et al, 2011b). However, the number of differentially expressed genes was an order of magnitude greater following exposure to the two MWCNTs than following exposure to nano-TiO 2 and nano-CB, indicating stronger potency of MWCNT.…”
Section: Discussionsupporting
confidence: 76%
“…Doses and time points were selected based on the previous and ongoing studies in our group (Bourdon et al, 2012b;Husain et al, 2013;Jacobsen et al, 2009;Poulsen et al, 2013;Saber et al, 2012Saber et al, , 2013. The consistency in doses and time points across many studies enabled comparison of responses after exposure to different nanomaterials.…”
Section: Dose Selectionmentioning
confidence: 99%
“…A wide variety of applications are being investigated for use in biomedical research 11 . This method could be utilized for assessment of different biological samples (such as various tissues types, bronchoalveolar lavage samples, and blood smears) that have been exposed to nanoparticles of a variety of elemental compositions [16][17][18][19] . Furthermore, this method is useful for studying nanoparticle biodistribution in vivo and in vitro, which is pertinent for nanoscale drug delivery studies 11 .…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that there is a positive z score (up regulation) associated with acute phase response signaling, and a negative z score (down regulation) associated with LXR/RXR activation, but neither is considered significant. Others have observed an up regulation of the acute phase response signaling pathway in response to TiO 2 NP exposure via gene expression analysis of mouse lung tissue[35, 36]. Husian and coworkers examined differentially expressed genes from mouse lung tissue after intratracheal instillation of low, medium, and high concentrations of TiO 2 NPs at 1, 3, and 28 days post exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of bronchoalveolar lavage fluid (BALF) from animal studies have demonstrated TiO 2 NP exposure increases inflammatory cells, such as neutrophils and lympohcytes; moreover, the observed increase of inflammatory cells was found to be dependent on days after exposure [30-33], dose [32-34], and method of introduction (whole body inhalation vs. intratracheal instillation) [33]. Furthermore, gene expression analyses of lung tissue have shown immune and inflammatory responses as a result of TiO 2 particle exposure [34-36]. Additionally, markers associated with oxidative and nitrosative stresses in the microcirculation increase [20-22, 25].…”
Section: Introductionmentioning
confidence: 99%